Критеріальні характеристики математичної культури майбутнього фахівця з програмної інженерії - Дубініна, Оксана Миколаївна (ІМА-прес, 2014)
У статті охарактеризовано, визначено та систематизовано критерії та ознаки, які розкривають структурні та функціональні компоненти математичної культури майбутніх інженерів індустрії програмної продукції, з урахуванням того, що вище означена культура являє собою своєрідний процес, в основі якого знаходиться взаємодія знань, навичок і переконань, придбаних в процесі формування акмеологічного, аксіологічно-мотиваційного, інформаційно-методологічного, гуманітарного, когнітивного, компетентнісного, креативного і рефлексивно-оціночного компонентів.

The article was described, defined and codified criteria and features that reveal their structural and functional components of mathematical culture of future engineers in software industry. Mathematical culture of the future engineer of software products industry is a kind of process, internal activity, which based on interaction, mutual transition and conjugation of knowledge, skills and beliefs acquired in the process of acmeological, axiologicaly motivational, informationally-methodological, humanitarian, cognitive, competence, creative and reflective-evaluative components. Thus, all components of mathematical culture are in inseparable unity and cooperation. The goal of mathematics education of students in the direction of training «software engineering» in author’s opinion is in formation of mathematical culture of the latter, which is the basis of development of their natural talent, ability to follow continuous self-improvement and application of mathematical knowledge in their future careers as a result provides stability of professionalism. Exploring the question of formation of mathematical culture during the training of future professionals in the field of software engineering in higher technical education we have come to a contradiction between the demand for high-level mathematical culture above mentioned professionals through the development of modern requirements of the industry and the lack of this problem in teaching science. The results in perspective for further research can be used for integrated qualimetry of the mathematical culture of the person, that in turn will give the opportunity to persistently improve the quality of higher engineering education in the speciality "software engineering".
Criteria specifications of mathematical culture of future specialists in software engineering
Keywords: вищі технічні навчальні заклади; критерії сформованості; математична культура особистості; програмна продукція; higher technical education; components of mathematical culture; formation criteria; mathematical culture of the person